Fostering Islamic Morality through Tahfidz Learning: Islamic Law - Yudi Kurniawan Saputra; Moatti Dylan; Dumaz Carmelo (Yayasan Adra Karima Hubbi, 2023)
Background. Tahfidz learning is a learning that can change the behavior of santriwan and santriwati and develop a potential that they have such as improving the reading of the Qur'an, increasing the memorization of the Qur'an. The tahfidz house is a place where students learn, foster and develop and apply the values contained in the Qur'an in everyday life such as at home, in the community and at school. Purpose. This tahfidz activity begins with prayer, then murojaah, memorizing the recitation of the Qur'an. Method. Data was obtained by giving teacher performance scales, teacher digital literacy, and online learning implementation scales. Results. The results of this tahfidz activity research begin with prayer, then murojaah, memorizing the recitation of the Qur'an. After memorizing the Qur'an, each student deposits his memorization one by one to the ustadz or ustadzah. After that the students and ustadz or ustadzah continue by playing the verse connection game in order to increase the enthusiasm of the students in memorizing so that they are not easily bored and bored, because in learning there are a lot of complaints and laziness when learning, let alone learning to memorize the Qur'an there are a lot of outside distractions. Conclusion. After the students take part in tahfiz learning, there are Islamic morals that can be applied, namely keistiqomahan, patience which is contrary to the previous morals of the students.